Enhancement of Blast Resistance of R.C Beams Using Micro/Nano Silica in Presence of Steel Fibers - Mahmoud Nawar; Kareem El-Awady; Hamdy Shehab; Ahmed Eisa (Fracture and Structural Integrity)
An analytical investigation using ABAQUS/Explicit dynamic analysis was carried out to investigate the effect of using Micro/Nano silica in the presence of steel fibers on improving the dynamic response of reinforced concrete beams. According to the results of Magnusson and Hallgren's experimental investigation, the FE model has been well verified and calibrated. The finite element test program was extended further to study the effect of tensile reinforcement ratio by (0.5%, 0.78%, and 1.13%) comparing with the enhancement of concrete’s material on the behavior of tested R.C beams under blast loading. The results where compared in terms of changes in the max deflection at mid-span and flexural toughness values. The results showed that the combination between the compressive and flexural characteristic of concrete is necessary in case of high steel reinforcement ratio to reduce the brittle behavior of the R.C structure element, especially when the R.C elements exposed to a high strain rate loading due to the addition value of (DIF) for steel reinforcement properties which make the element stiffer than usual, compared with quasi-static loading condition.